2018
DOI: 10.1080/13875868.2017.1298113
|View full text |Cite
|
Sign up to set email alerts
|

Rhetorical shadows: The conceptual representation of incongruent shadows

Abstract: This article addresses the topic of conceptual representation of shadows. We analyze several examples of contemporary imagery, taken from advertising and cartooning, to shed light on the way shadow depictions are used as rhetorical devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Finally, we demonstrated that the BA-construction intersects with a hierarchy of caused-change constructions. These patterns and their relations provide 11 A third visual construction that is capable of suggesting caused-change is discussed in Schilperoord and Van Weelden (2018), and operates on incongruent shadow depiction. The ad in question is one for an energy supplement and shows a young, energetically running woman dressed in sports outfit.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we demonstrated that the BA-construction intersects with a hierarchy of caused-change constructions. These patterns and their relations provide 11 A third visual construction that is capable of suggesting caused-change is discussed in Schilperoord and Van Weelden (2018), and operates on incongruent shadow depiction. The ad in question is one for an energy supplement and shows a young, energetically running woman dressed in sports outfit.…”
Section: Discussionmentioning
confidence: 99%
“…That is, the shadow reveals the 'true nature' of its caster (the topic of the message) (for rhetorical shadows, cf. Schilperoord and Van Weelden, 2018).…”
Section: From 'Computer Virus' To 'Go Viral'mentioning
confidence: 99%
“…Shadows are always present but, depending on the object and how the light is cast, their shapes and sizes change, and they can become more and less visible. Shadows draw attention to the casting object, the source of light, and the surface on which they fall (Schilperoord & van Weelden, 2018). In this article, we approach family life as the surface on which institutional placement (because of its emotional and relational impacts) casts its shadows.…”
Section: Introductionmentioning
confidence: 99%